DAMPAK ALIH FUNGSI LAHAN PERKEBUNAN KARET MENJADI PERKEBUNAN KELAPA SAWIT MENJADI PERKEBUNAN KELAPA SAWIT BAGI KESEJAHTERAAN PETANI DESA BANGUN HARJO KECAMATAN PELEPAT ILIR KABUPATEN MUARA BUNGO - Sidik Eko Saputro (JURNAL BUANA, 2022)
ABSTRACT This study aims to (1) how the rubber plantations were converted into oil palm plantations from 2015-2020 in Bangun Harjo village (2) What is the background that causes rubber farmers to convert their land into oil palm plantations. Then (3) What is the impact on the welfare of rubber farmer families after turning into oil palm farmers in Bangun Harjo village. This research is a Mix Methods research. The number of respondents using purposive sampling is 17 farmers. The results of this study indicate that changes in the area of ​​​​rubber in Bangun Harjo village, Pelepat Ilir sub-district, Muara Bungo regency every year always decreases, while the area of ​​​​oil palm land increases every year, the background of the cause of rubber farmers switching functions to oil palm farmers is because the work of rubber farmers must be done. every day, and some rubber plants are getting old and have an impact on reducing rubber productivity. Meanwhile, palm oil works only once in 2 weeks and the price of palm oil always increases. The impact of the welfare of rubber farmer families after the conversion of land to oil palm farmers in Bangun Harjo village, Pelepat Ilir district, Muaro Bungo district is a positive impact for farmers, 16 farmers belong to very prosperous families (KS III Plus) and 1 farmer belongs to prosperous family (KS III).